Utility of sequential organ failure assessment score in predicting outcome for patients with peritoneal sepsis - Razack, G. S. Abdul; Kavya, T.; Manjunath, B. D.; Ali, Mohammed Arafath; Avinash, K.; Harindranath, H. R. (International Surgery Journal, 2019)
Background: Severe complicated intra-abdominal sepsis (SCIAS) is a worldwide challenge with increasing incidence. The sequential organ failure assessment (SOFA) score numerically quantifies the number and severity of failed organs. We examined the utility of the SOFA score for assessing outcome of patients with severe peritoneal sepsis. Methods: This is a prospective observational study. A total of 100 patients who presented to emergency department of Victoria hospital with features suggestive of peritoneal sepsis from January 2018 to August 2018 were included in the study. The presence of organ dysfunction was assessed using a sequential organ failure assessment (SOFA). Clinical, microbiologic, and laboratory factors were considered for assessing the outcome. Results: Forty-two patients had two or more sites of infection on admission. Bacteraemia was confirmed in 20 patients. 88 patients were surgical. The median age of patients was 69 years. Males being more commonly affected than females. Twenty-eight days survival rate was 41%. The incidence of organ dysfunction on day 1 was noted more frequently for renal, cardiovascular, and neurological systems. SOFA score on day 1 and day 3 were significantly higher in non-survivors than those in survivors. Patients with three and higher number of organ systems with dysfunction had a lower survival rate than the subgroups of patients with one or two organ systems with dysfunction. Conclusions: The SOFA score provides potentially valuable prognostic information on in hospital survival when applied to patients with severe peritoneal sepsis.